2022
DOI: 10.1021/acs.jcim.2c00155
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Peer Mentoring Networks for Developing Leaders and Inspiring Change

Abstract: A peer-mentoring network, funded by the National Science Foundation ADVANCE program, profoundly impacted the career trajectory of five women chemistry faculty at predominantly undergraduate institutions. By providing each other support, encouragement, information, and accountability, we advanced our careers, became leaders in our own right, and implemented change at our institutions. To extend this benefit to more women STEM faculty, we have developed and implemented a model to support 74 faculty and administr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Collaboration and teamwork are not just generic virtues in scientific research, they are essential components of incorporating undergraduates into behavior genetics research. Encouraging collaboration among undergraduate researchers, as well as between undergraduates and more experienced lab members, promotes a supportive learning environment and helps students develop effective communication and teamwork skills (Bruce et al, 2022;Glaser et al, 2006). This collaboration also enables more experienced students to mentor less experienced students, which allows the more experienced student to develop their own mentoring skills (Dolan & Johnson, 2010), while also saving time for the PI.…”
Section: Supporting First-generation and Neurodivergent Students Prov...mentioning
confidence: 99%
“…Collaboration and teamwork are not just generic virtues in scientific research, they are essential components of incorporating undergraduates into behavior genetics research. Encouraging collaboration among undergraduate researchers, as well as between undergraduates and more experienced lab members, promotes a supportive learning environment and helps students develop effective communication and teamwork skills (Bruce et al, 2022;Glaser et al, 2006). This collaboration also enables more experienced students to mentor less experienced students, which allows the more experienced student to develop their own mentoring skills (Dolan & Johnson, 2010), while also saving time for the PI.…”
Section: Supporting First-generation and Neurodivergent Students Prov...mentioning
confidence: 99%
“…18,19 Ample evidence suggests that women in academia either leave or become stalled at the associate professor level at rates higher than men. 20 Why Diversity is Important in Academia. To align the STEM pipeline with population demographics, we need faculty who reflect those demographics, that is, our students benefit from role models to whom they can relate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent studies from the European Union suggest that among doctoral graduates, women are approaching gender parity, but are still underrepresented in technical fields (24.9%) and only 26.2% advance to full professor . In US academia more generally, data from the 2005–2006 American Faculty Compensation Survey indicated that only 24% of full professors were women. Even after controlling for factors such as productivity, social networks, and other human, social, and structural capital, a logistical regression analysis on the National Study of Postsecondary faculty data set by Perna indicated that women were less likely to achieve the rank of full professor. , Ample evidence suggests that women in academia either leave or become stalled at the associate professor level at rates higher than men …”
Section: Introductionmentioning
confidence: 99%
“…As editors we are committed to foster an environment inclusive of all identities, regardless of sexual orientation, ethnicity, disability, geographical location, and institutional prestige. These values are reverberated by one Article, two ViewPoint, and one Perspective articles taking up persistent issues to be overcome , but also highlighting successful initiatives for advancing the careers of female scientists in chemistry. , Cascella and Soares examined the status of bias based on gender identity and geographic affiliation in academia and scholarly publication, providing recommendations for the greater inclusion of the LGBTQIA+ scientific community and scientists located outside major geographical hubs of science . It also underlined the urgent need for research on these biases that enables the creation and implementation of effective institutional policies for change.…”
mentioning
confidence: 99%
“…Tripathi and Goshist overviewed major progresses and the remaining glass ceilings faced by female scientists in chemistry and advised on initiatives at various institutional levels to cease the leaky pipeline of women in STEM . Bruce and coauthors reported on the success of a peer-mentoring network funded by the National Science Foundation (NSF) to facilitate the exchange of experiences, support, and information among female chemistry faculty at undergraduate institutions . The initiative not only advanced the careers of the faculty but led to the implementation of institutional changes.…”
mentioning
confidence: 99%